Determinants of Customers' Perceived Value in the Fast Food Industry for Global Brands in Malaysia - Jalal, Hanaysha; Haim, Hilman; Zahari, Abu Bakar; Lee, Khai Loon (IGI Global, 2019)
The purpose of this research was to investigate the effect of food quality, customer service, physical environment, and price fairness on perceived value in the fast food industry. A survey method was used for the collection of desired information from the visitors of global fast food restaurants in the East Coast region of Malaysia. The returned questionnaires were analyzed by SPSS and structural equation modeling (PLS-SEM). Overall, the findings showed that the impact of food quality on perceived value is positive. The results also showed that the effect of customer service on perceived value is insignificant. The outcomes also proved that physical environment has a significant positive impact on perceived value. Finally, the findings indicated that price fairness has a positive effect on perceived value. These results enhance the understanding towards the significance of the selected factors in influencing customers' perceived value in the fast food industry.